Platelet-Derived Growth Factor Regulates the Biological Behavior of Oral Mucosal Fibroblasts by Inducing Cell Autophagy and Its Mechanism - Wang J; Yang L; You J; Wen D; Yang B; Jiang C (Dove Medical Press, 2021)
Jie Wang,1,2 Lina Yang,2 Jialing You,2 Dada Wen,2 Bo Yang,2 Canhua Jiang1 1Department of Oral and Maxillofacial Surgery, Xiangya Hospital, Central South University, Changsha, 410078, People's Republic of China; 2Department of Immunology, Xiangya School of Medicine, Central South University, Changsha, 410078, People's Republic of ChinaCorrespondence: Canhua JiangDepartment of Oral and Maxillofacial Surgery, Xiangya Hospital, Central South University, 87 Xiangya Road, Changsha, 410078, Hunan, People's Republic of ChinaTel/Fax +86-731-89753046Email wj0988@csu.edu.cnObjective: To explore the effect of platelet-derived growth factor (PDGF) on oral mucosal fibroblast autophagy and further elucidate the molecular mechanism by which PDGF-BB regulates the biological behavior of oral mucosal fibroblasts by inducing autophagy.Methods: Primary oral mucosal fibroblasts were isolated and cultured by the tissue block and trypsin methods and identified by indirect immunofluorescence vimentin detection. We detected the autophagy marker Beclin-1 and fibrosis marker Col-I of the primary oral mucosal fibroblasts at different time points after stimulating the fibroblasts with different PDGF-BB concentrations by Western blotting and determined the best experimental concentration and stimulation time of PDGF-BB. Then, indirect immunofluorescence, Western blotting, and quantitative real-time polymerase chain reaction (PCR) were used to detect the effect of PDGF-BB on the expression of autophagy-related and fibrotic proteins before and after 3-methyladenine (3-MA) intervention. Additionally, the effect of 3-MA on the proliferation and migration of primary oral mucosal fibroblasts stimulated by PDGF-BB was detected by the MTT method and a scratch experiment. The effect of PDGF-BB on Beclin-1 and phosphatidylinositol-3 kinase class 3 (PI3KC3) interaction was detected by co-immunoprecipitation.Results: The results demonstrated that PDGF-BB could induce autophagy of the oral mucosal fibroblasts, showing a certain time and dose correlation. It induced cell autophagy through Beclin-1 and PI3KC3 interaction to promote the proliferation, migration, conversion, and collagen synthesis of the fibroblasts. However, 3-MA inhibited the combination of Beclin-1 and PI3KC3 and weakened the fibroblasts' proliferation, migration, conversion, and collagen synthesis activities.Conclusion: Overall, PDGF-BB induces autophagy through the Beclin-1 pathway to regulate the biological behavior of oral mucosal fibroblasts.Keywords: PDGF-BB, primary oral mucosal fibroblasts, autophagy, 3-MA, biological behavior, signaling pathway